Interactions of Alginate-Deferoxamine Conjugates With Blood Components and Their Antioxidation in the Hemoglobin Oxidation Model - Sun, Tong; Guo, Xi; Zhong, Rui; Wang, Chengwei; Liu, Hao; Li, Hao; Ma, Lu; Guan, Junwen; You, Chao; Tian, Meng (Frontiers in Bioengineering and Biotechnology, 2020)
While deferoxamine (DFO) has long been used as an FDA-approved iron chelator, its proangiogenesis ability attracts increasing number of research interests. To address its drawbacks such as short plasma half-life and toxicity, polymeric conjugated strategy has been proposed and shown superiority. Owing to intravenous injection and application in blood-related conditions, however, the blood interactions and antioxidation of the DFO-conjugates and the mechanisms underlying these outcomes remain to be elucidated. In this regard, we analyzed the interactions of three different molecular-weight (MW) alginate conjugates (ADs) with blood components, including red blood cells (RBCs), coagulation function, complement and platelet. To prove the antioxidant activity of ADs, we used hemoglobin oxidation model in vitro. The interaction of ADs with red blood cells (RBCs) did not cause hemolysis while showed reversible aggregation and normal deformability ability. However, the coagulation time, particularly APTT and TT, were significantly prolonged in a dose-dependent manner, while fibrinogen was dramatically decreased, suggesting ADs could dominantly inhibit the intrinsic pathways in the process of coagulation. The dose-dependent anticoagulation might be related with the functional groups along the alginate chains. The complements, C3a and C5a, were activated by ADs in a dose-dependent manner through alternative pathway. For platelet, ADs slightly suppress the activation and aggregation only at low concentration. Based on above results, the cross-talking among coagulation, complement and platelet induced by ADs was proposed. The antioxidation of ADs through iron chelation was proved and the antioxidant activity was shown in a MW-dependent manner.